MVC Concept in the Development of Information System for Rental Office Utilities Cost - Sudradjat, Adjat; Atmaja, Rahdian Kusuma; Ramadan, Rino; Ispandi, Ispandi (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2019)
The calculation of the utilities cost of rental office in an office building that is still processed manually and conventionally is certainly troublesome for the building manager. Data processing by using office applications such as spreadsheets becomes ineffective when the number of tenants is increasing and transaction data coming in continues to grow. It causes stakeholders to often experience delays in obtaining the required reports. The research aims to build an application which can be used easily and able to provide information quickly and accurately in the process of calculating the utilities cost of rental office, which consists of the usage costs of electricity, water and gas. The application is developed by using MySQL database and PHP, HTML, CSS, Jquery as programming languages. It also applies the concept of MVC (Model-View-Controller) to the CodeIgniter framework and using agile method in developing the system. The research resulted in a web-based application of the utilities cost information system that is useful for building managers in the process of recording and calculating utilities cost automatically, so it can produce reports quickly and accurately. The advantage of the web-based application is that it allows stakeholders to obtain the required reports because they can be accessed directly online, so that the use of electricity, water and gas at rental offices can be well controlled.